2018
DOI: 10.3892/ol.2018.8660
|View full text |Cite
|
Sign up to set email alerts
|

18F‑FDG PET/CT characteristics of pulmonary sclerosing hemangioma vs. pulmonary hamartoma

Abstract: Abstract. The radiological features of pulmonary sclerosing hemangioma (PSH) and pulmonary hamartoma are poorly specified. Thus, the present study aimed to compare and analyze the characteristics of fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) in PSH versus pulmonary hamartoma.18 F-FDG PET/CT characteristic findings of 12 patients with PSH and 14 patients with pulmonary hamartoma were retrospectively reviewed. A total of 12 lesions were detected from the 12 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 24 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…The presence of 18 F-FDG uptake in inflammatory or infective diseases, other than malignant diseases, reduces the specificity of PET/CT ( 8 ). Low 18 F-FDG uptake can be observed in pulmonary hamartomas ( Figure 2 ) ( 9 , 10 ). Ergonul et al ( 9 ) reported 18 F-FDG PET/CT findings of 106 patients with benign lung lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 18 F-FDG uptake in inflammatory or infective diseases, other than malignant diseases, reduces the specificity of PET/CT ( 8 ). Low 18 F-FDG uptake can be observed in pulmonary hamartomas ( Figure 2 ) ( 9 , 10 ). Ergonul et al ( 9 ) reported 18 F-FDG PET/CT findings of 106 patients with benign lung lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The SUV max of 19 hamartomas ranged from 0 to 4.5 ( 9 ). Jiang et al ( 10 ) reported the 18 F-FDG PET/CT findings of 14 pulmonary hamartomas with a mean diameter of 1.7±0.8 cm (range, 0.7-3.1 cm), and the mean SUV max of lesions was 1.5±0.6 (range, 0.7-2.6) ( 10 ). Similarly, in the present study, the mean SUV max was 1.65±0.9 (range, 0-3.38).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that SUVmax value of hamartomas was lower when compared to the other benign conditions including granulomatous lung disease, reactive lymph nodes and interstitial lung disease. Jiang et al 14 analysed PET/CT images of 14 patients with hamartoma and found mean SUV max value as 1.5±0.6 (range between 0.7 and 2.6). In our study, mean SUVmax value of 22 lesions was 1.6±1.0 (range between 0 and 3.2).…”
Section: Discussionmentioning
confidence: 99%
“…Hamartomas, including endobronchial ones, incline to stay below-radar in F-18 FDG PET/CT [7,8]. Initial examination and evaluation of all findings, including CT scan and SUVmax value, directed the route towards low activity nodules of the lung: Typical carcinoid, pulmonary adenoma, bronchioloalveolar carcinoma and of course, endobronchial hamartoma [9][10][11].…”
Section: Discussionmentioning
confidence: 99%